TREATMENT RESULTS OF ENDOMETRIAL CANCER BY LAPAROSCOPIC SURGERY AT NGHE AN GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2022)
The purpose: To evaluate the results of laparoscopic surgery in the treatment of endometrialcancer at Nghe An General Friendship Hospital from June 2020 to June 2022.Subjects and methods: Including 32 cases of endometrial cancer diagnosed and treated bylaparoscopic surgery at Nghe An General Hospital. Study design: retrospective description.Results: 4 patients with cancer in situ, 21 patients with stage I cancer, the mean age was 56.8years old. The average surgery time was 150 minutes. The mean number of pelvic lymph nodesremoved was 1.52 right iliac nodes and 1.22 left iliac nodes.Conclusion: Laparoscopic surgery in endometrial cancer is safe and effective.
Keywords: Endometrial cancer, laparoscopic surgery, open surgery.